2013
DOI: 10.1002/jee.20011
|View full text |Cite
|
Sign up to set email alerts
|

Indispensable Resource? A Phenomenological Study of Textbook Use in Engineering Problem Solving

Abstract: Background Textbooks play an important role in engineering education, influencing instructors' pedagogical approaches and providing much of the information students learn. Research has explored students' recollections of the roles that textbooks played in their educational experiences, but how students actually use textbooks remains largely unexplored.Purpose This phenomenological study describes engineering students' textbook use during problem-solving activities. This study directly examined how students emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 32 publications
0
48
0
2
Order By: Relevance
“…Some students opt to use the Internet for free rather than add hundreds of dollars of books to growing tuition costs [18]. Therefore, electronic resources at a lower price, such as the zyBook discussed here, provide another alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Some students opt to use the Internet for free rather than add hundreds of dollars of books to growing tuition costs [18]. Therefore, electronic resources at a lower price, such as the zyBook discussed here, provide another alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, past research examining transportation engineering practice identified the textual resources utilized in this study as being relevant to practice and academia 41,42,16,43,44 . For example, a previous study examined syllabi of introductory transportation engineering courses within the United States, and identified 7 textbooks (with two of the textbooks being represented in various editions) utilized within such courses 41 .…”
Section: Sampling Of Textual Resourcesmentioning
confidence: 94%
“…Indeed, past studies note the role of these resources in learning. For example, Lee and colleagues examined the role of textbooks in students' problem-solving processes noting that students included in the phenomenological study tended to utilize the textbooks for gaining information on problem constraints and as models for solutions on examples provided in the textbooks 16 . Other studies of the role of symbols, visual representations, and inscriptions note the central role of these tools in mediating communication and knowledge sharing in not only engineering, but also in mathematics and the sciences 17,18,19,20 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, worked examples and homework problems are included in most engineering textbooks. However, the invention and mass production of the smartphone and simple access to factual information through Internet search engines, including Google, has changed how students obtain most of the information found in textbooks [1]. The price of textbooks has risen dramatically to more than $200 per traditional hard cover book used in an engineering course, and some student opt to use the Internet for free than add hundreds of dollars of books to their growing tuition costs.…”
Section: Introductionmentioning
confidence: 99%
“…Multimedia presentations led to improved test scores compared to students using text-based presentations [3]. Students have also shown preference to the diverse set of resources on the Internet to a single, text-heavy textbook [1,3]. More recently, interactive web-based content led to statistically significant learning gains compared to static web-based content [4,5].…”
Section: Introductionmentioning
confidence: 99%